Dynamics of photoinduced interfacial electron transfer and charge transport in dye-sensitized mesoscopic semiconductors - Thorsmolle, V; Wenger, B; Teuscher, J; Bauer, C; Moser, J (2007)
Molecular systems designed for the conversion of solar energy offer ideal models in the study of the kinetics of light-induced electron transfer at surfaces. Due to their high porosity, nanocrystalline oxide semiconductor films allow investigations of interfacial and lateral charge transfer processes that are barely detectable on flat surfaces. Although it has proven to be very promising, the redox photochemistry of the metal oxide I molecular monolayer I electrolyte interface is still a largely unexplored scientific domain, offering huge potential for investigation and exploitation of physical and chemical processes. Carrier trapping and charge transport are also key to the efficiency of molecular photonic devices. Carrier dynamics and transport in unconventional media are studied utilizing THz time domain spectroscopy. We summarize here some aspects of the work currently carried out in these fields as part of our continued effort in the fundamental study of the dynamics of photoinduced electron transfer processes. © Schweizerische Chemische Gesellschaft.